The Influence of Green Marketing and Environmental Awareness on Purchase Decisions for Eco Friendly Tumbler Products - Nanda Ariska; Zultoni Lubis; Fadhilah Syafitri Rangkuti; Feny Feny; Nabila Mutia Syifa (Brilliant International Journal Of Management And Tourism, 2026)
This study aims to analyze the influence of green marketing and environmental awareness on purchasing decisions for eco-friendly tumblers among Generation Z in Indonesia. Using a quantitative approach through a survey of 210 respondents aged 18-27 years, this study measured perceptions of the green marketing mix (product, price, place, promotion), levels of environmental awareness, and purchasing decisions using a 5-point Likert scale. Data were analyzed using descriptive statistics and multiple regression analysis with the help of SPSS version 25. The results showed that green marketing had a positive and significant influence on purchasing decisions (β = 0.387, p < 0.001), with the green product orientation dimension providing the largest contribution. Environmental awareness also had a positive and significant influence on purchasing decisions (β = 0.445, p < 0.001), even with a slightly greater contribution than green marketing. Respondents showed a very high level of environmental awareness (mean = 4.35) and a positive perception of green marketing (mean = 4.12), with 87.6% of respondents having owned or having purchased an eco-friendly tumbler. However, this study also identified a knowledge-intention-behavior gap, with price sensitivity (mean = 3.89) and concerns about greenwashing (44.8% of respondents) being the main barriers. These findings offer practical implications for companies to develop green marketing strategies that are authentic, transparent, and consider the local context of the Indonesian market, as well as for policymakers to encourage infrastructure supporting sustainable consumption, such as refill stations and institutional incentives.